Challenges in obtaining and assessing salivary cortisol and α-amylase in an over 60 population undergoing psychotherapeutic treatment for complicated grief: Lessons learned - Bell, Jesse M. (Clin Nurs Res, 2020)
Biomarkers may serve as objective measures in complicated grief (CG) potentially capturing responses to stress reduction treatment. This paper reports challenges in obtaining and assessing salivary cortisol and α-amylase (sAA) for a recent randomized clinical trial. Within-session changes in salivary cortisol and sAA for 54 older adults with CG who received Accelerated Resolution Therapy were compared with perceived stress measured by Subjective Units of Distress Scale. Bivariate correlations and multiple regressions examined changes in biomarkers. Protocols, study logs, and audit reports identified challenges. Challenges included obtaining unstimulated passive drool salivary samples and their analyses. Our sample of older females on multiple medications may have resulted in a perfect storm of moderating and intervening variables which affected the stress response. This paper contributes to the discussion on designing clinical trials for older adults which must account for physiologic changes, multimorbidity, and polypharmacy common in this population and makes recommendations moving forward.